1984
DOI: 10.1002/hep.1840040608
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Reovirus Type 3 in the Porta Hepatis of an Infant with Extrahepatic Biliary Atresia: Ultrastructural and Immunocytochemical Study

Abstract: This report describes immunocytochemical and ultrastructural methods which led to the identification of Reovirus type 3 (Reo-3) in the porta hepatis of a patient with extrahepatic biliary atresia. The study indicates that Reo-3 antigenic sites are demonstrable by the avidin-biotinylated complex peroxidase method following formalin fixation and paraffin embedding, but are destroyed by freezing and thawing prior to fixation. Deparaffinization of the block and subsequent rembedding in epon-araldite did not alter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
1
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 5 publications
1
39
1
1
Order By: Relevance
“…Some studies have demonstrated a correlation between the presence of anti-reovirus antibodies and biliary atresia, while others have not (16)(17)(18)(19)(20)(21)(22)(23). Our findings may explain the discordance between anti-reovirus seropositivity and biliary atresia.…”
Section: Figurementioning
confidence: 52%
“…Some studies have demonstrated a correlation between the presence of anti-reovirus antibodies and biliary atresia, while others have not (16)(17)(18)(19)(20)(21)(22)(23). Our findings may explain the discordance between anti-reovirus seropositivity and biliary atresia.…”
Section: Figurementioning
confidence: 52%
“…Two types of evidence support a viral role in the pathogenesis of biliary atresia. The first type is patient-based studies in which viruses, including reovirus (11,19,20), cytomegalovirus (7,9), human papillomavirus (8), Epstein-Barr virus (10), and rotavirus (27), were found in the livers of infants with biliary atresia. The second type of evidence is the murine model of inflammatory cholangiopathy in which newborn mice injected with rhesus rotavirus (RRV) develop extrahepatic biliary obstruction and death (28).…”
mentioning
confidence: 99%
“…However, research suggests that reoviruses may be associated with potentially more severe illnesses. Reoviruses have been linked to neonatal hepatitis, extrahepatic biliary atresia, meningitis, and myocarditis (9,16,25,28,29). Also, immunocompromised, young, and elderly individuals may become susceptible to severe bacterial respiratory disease due to an initial reovirus infection (5).…”
mentioning
confidence: 99%